The Benefits of Expert Instruction in Microsurgery Courses - Paladino, Joseph R.; Gasteratos, Konstantinos; Akelina, Yelena; Marshall, Brittany; Papazoglou, Lysimachos G.; Strauch, Robert J. (Journal of Reconstructive Microsurgery, 2020)
Background Microsurgery requires repeated practice and training to achieve proficiency, and there are a variety of curriculums available. This study aims to determine the importance of an expert instructor to guide students through procedures. We compared student proficiency across two microsurgery courses: one with (Columbia University, United States [CU] cohort) and one without a dedicated microsurgery instructor (University of Thessaloniki, Greece [UT] cohort).Methods Students were divided into two cohorts of 22 students (UT cohort) and 25 students (CU cohort). Student progress was evaluated by examining patency (lift-up and milking tests), anastomotic timing, and quality (Anastomosis Lapse Index [ALI]) of end-to-end arterial and venous anastomoses on day 1 and again on day 5. Chi-squared tests evaluated patency immediately and 30 minutes postoperation. t-Tests evaluated anastomotic timing and ALI scores. p-Values < 0.05 were considered significant.Results We evaluated progress within and between each cohort. Within the CU cohort, the quality of the arterial and venous anastomosis improved, respectively (by 54%, p = 0.0059 and by 43%, p = 0.0027), the patency of both the arterial and venous anastomosis improved, respectively (by 44%, p = 0.0002 and by 40%, p = 0.0019), and timing of arterial and venous anastomosis reduced respectively (by 36%, p = 0.0002 and by 33%, p = 0.0010). The UT cohort improved the quality of their arterial anastomoses (by 29%, p = 0.0312). The UT cohort did not demonstrate significant improvement in the other above-mentioned parameters. The CU cohort improved materially over the UT cohort across categories of quality, patency, and timing.Conclusion There are clear benefits of an expert instructor when examining the rate of progress and proficiency level attained at the conclusion of the course. We suggest students who are seeking to maximize proficiency in microsurgical procedures enroll in courses with an expert instructor.
Keywords: anastomosis lapse index; student learning; anastomotic timing; microsurgical training; expert instructor